Expression of miRNA in the Semitendinosus Muscle of Cattle Breeds with Varying Intramuscular Fat Deposition - Ciecierska, Anna; Gorji, Abdolvahab Ebrahimpour; Majewska, Alicja; Sadkowski, Tomasz (Genes, 2025)
Background: This study investigates the expression of microRNAs (miRNAs) in the semitendinosus muscle of cattle breeds with varying intramuscular fat (IMF) deposition to identify key miRNA regulators of beef marbling, utilizing Hereford (HER; higher IMF) and Holstein-Friesian (HF; moderate IMF) bulls, and Limousin (LIM; low IMF) bulls with lower IMF in the semitendinosus muscle. Methods: MicroRNA profiling used custom bovine microarrays and the Agilent software. The selected miRNAs, miR-34a, miR-149-5p, miR-208b, miR-499, miR-660, and miR-1343-5p, were chosen for validation using real-time PCR, confirming their differential expression. Target prediction utilized miRWalk, while functional and pathway analyses were conducted using the DAVID database to interpret biological relevance. Results: Microarray analysis identified 51 differentially expressed miRNAs. Among these, 24 exhibited consistent expression patterns in high-marbling breeds compared to the low-marbling LIM breed. Bioinformatic analysis of the 4941 predicted target genes of these 24 miRNAs revealed significant enrichment in pathways crucial for marbling, including the adipocytokine, AMPK, MAPK, and PI3K-Akt signaling pathways, as well as biological processes such as cell differentiation and lipid homeostasis. Notably, miR-34a and miR-149-5p emerged as significant regulators, with miR-34a targeting genes like SIRT1, HMGA2, PTPN11, VEGFA, FGF1, FGF2, and BRAF, and miR-149-5p influencing adipogenesis and lipid metabolism through its association with crucial KEGG pathways such as PI3K–Akt, MAPK, PPAR, TGF-β, cAMP, and Wnt signaling, all of which collectively influence adipocyte differentiation, lipid metabolism, cell cycle control, and angiogenesis. Conclusions: The findings underscore identified miRNAs’ possible coordinated regulatory role, particularly miR-34a and miR-149-5p, in the complex molecular mechanisms governing IMF deposition in cattle, providing potential targets for improving beef quality.